Pure Spinal Epidural Cavernous Hemangioma: A Rare Cause of Thoracic Myelopathy - Sukriti Das; Md Mamunur Rashid; Saiful Islam; Shamit Barua; Md Motasimul Hasan (Bangladesh Journal of Neurosurgery, 2024)
Cavernous hemangiomas mostly occur in intracranial structures but they also may occur in the spine very rarely. Even if found, spinal hemangiomas are commonly vertebral origin and solely epidural hemangiomas not originating from the vertebral bone are very rare. Our case is a 65-year-old man presented to us with progressive paraparesis from six months with motor power 3/5 in both lower extremities. The pathology was total epidural spinal hemangioma at D9-10 vertebral level with typical myelopathy like presentation. Bang. J Neurosurgery 2024; 13(2): 149-151